Nonlinear control for a diesel engine: A CLF-based approach - Kuzmych, Olena; Aitouche, Abdel; El Hajjaji, Ahmed; Bosche, Jerome (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we propose a control Lyapunov function based on a nonlinear controller for a turbocharged diesel engine. A model-based approach is used which predicts the experimentally observed engine performance for a biodiesel. The basic idea is to develop an inverse optimal control and to employ a Lyapunov function in order to achieve good performances.
Keywords: turbocharged diesel engine; control Lyapunov function; nonlinear control design; stability analysis; diesel virtual test bench